Eine kompagnie Soldaten, die sich den Arbeiter und Soldaten Rat zur Verfügung gestellt hat. Aus: Album XI
Eine kompagnie Soldaten, die sich den Arbeiter und Soldaten Rat zur Verfügung gestellt hat. Aus: Album XI.